Perfil de nutrientes de productos alimentarios eximidos de la aplicación de advertencias en el frente del envase durante la primera etapa de la Ley de alimentación saludable en Perú: estudio de caso - Jaime Delgado Zegarra; Fabio da Silva Gomes (Pan American Health Organization, 2021)
Objective. Identify the nutritional profile of food products exempted from presenting one or more front-ofpackage nutritional warnings during the first stage of Law 30,021 on the Promotion of Healthy Eating for Children and Adolescents in Peru. Methods. Data were collected on 188 products from points of sale in the city of Lima. The convenience sample included products that until September 17, 2021 were exempted by the legislation from presenting any of the warning labels for sugar, sodium, or saturated fats. An assessment was made of the proportion of products that would be required to apply one or more warning labels when the second stage of the legislation takes effect. It was also calculated how many products exempted from the application of warning labels contain excess sugar, sodium, or saturated fats, according to the criteria of the Pan American Health Organization (PAHO). Results. 76.1% of the products exceeded at least one of the thresholds for sugar, sodium, or saturated fats that entered in force in September 2021. The proportion of products that the law exempts from warnings and that contain excess sugar, sodium, or saturated fats according to PAHO will be 4.2, 3.4, and 2.3 times lower, respectively, in the second stage. Conclusion: During the first stage of the law's entry into force, 58%, 42%, and 28.2% of the products exempted from the presentation of warning labels contained excess sugar, saturated fats, or sodium, respectively, according to PAHO.